Petroleum geology : north-west Europe and global perspectives : proceedings of the 6th Petroleum Geology Conference held at the Queen Elizabeth II Conference Centre, London, 6-9 October 2003 - Doré, A. G.; Vining, B. A.; Burley, Stuart D. (Petroleum Geology Conference series ;, 2005)
These conference proceedings are presented in the thematic format of the conference itself, and the majority of papers presented in the conference appear as scientific contributions in the proceedings.